(untitled) (Research, Society and Development, 2023)
Chronic non-progressive encephalopathy, commonly called cerebral palsy, is caused by permanent damage to the developing brain. It is considered the most common cause of motor impairment in childhood. Its origin is heterogeneous and complex, and may be caused by prenatal, perinatal or postnatal risk factors. Given this context, along with the researcher’s experiences in the process of territorialization in the city of Milagres - Ceará, the following question arose: how is the profile of users with cerebral palsy treated in primary health care units in this municipality configured? The study aims to analyze the sociodemographic and clinical profile of users with cerebral palsy treated at primary health care units in the municipality of Milagres, Ceará. This is a cross-sectional, descriptive study with a quantitative approach. The study population consisted of eleven users and the sample resulted in six users. Data analysis was performed using SPSS 20.0. It was evidenced that the majority of the interviewees had a classification in the ICD 10-G80 and a predominance of spastic-type tonus. We found musculoskeletal disorders, behavioral disorders, respiratory disorders and epilepsy in the interviewees. Half of the users attended some rehabilitation service and the vast majority only received physical therapy. It is suggested that public policies on curative and preventive health be intensified and directed towards the particularities of users with cerebral palsy and their families, as well as new research being carried out to support these public health policies, in order to optimize these users’ access to specialized therapeutic services.